1997
DOI: 10.1007/s004310050661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of red cell transfusion on pulmonary blood flow and right ventricular systolic time intervals in neonates

Abstract: These results suggest that neither pulmonary artery pressure nor right ventricular function changed as a result of transfusion in spite of rising blood volume and blood viscosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…From a hemodynamic point of view, markers of higher pulmonary vascular resistance, such as more elevated pulmonary artery systolic pressure or a persistent notched left pulmonary arterial flow pattern [13] , were no longer observed after transfusion. Thus, with regard to respiratory status and right ventricular function, RBCT appeared to be as safe as when performed after the 1st postnatal month [20] .…”
Section: Discussionmentioning
confidence: 99%
“…From a hemodynamic point of view, markers of higher pulmonary vascular resistance, such as more elevated pulmonary artery systolic pressure or a persistent notched left pulmonary arterial flow pattern [13] , were no longer observed after transfusion. Thus, with regard to respiratory status and right ventricular function, RBCT appeared to be as safe as when performed after the 1st postnatal month [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal RBCs therefore do not possess specific properties that influence blood viscosity (17). Opposite to exchanging neonatal RBCs with adult RBCs, transfusing anemic preterm infants does increase blood viscosity by 33% and also blood volume (18).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the short-term cardiorespiratory effects of transfusions in normotensive preterm infants during the early neonatal period. Previous studies on the effects of 10-20 ml/kg red cell transfusions have been performed after the neonatal period in anaemic infants [1,2,4,8,9,13,14,26]. A decrease in cardiac output has been observed in some studies [8,13], whereas others have reported no significant effect on cardiac output [1,2,4].…”
Section: Discussionmentioning
confidence: 93%
“…A decrease in cardiac output has been observed in some studies [8,13], whereas others have reported no significant effect on cardiac output [1,2,4]. Nelle et al [14] reported no change in non-invasively measured blood pressure. A decrease in HR after red cell transfusion has been more consistently reported in anaemic subjects [8,9,13,14,26], most probably explained by mitigation of tissue hypoxia and concomitant tachycardia [27].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation